Evaluating the efficiency of warehouse using data envelopment analysis (DEA) - Natasha, Abdul Raoff (2015)
This study discusses about modeling the efficiency of the warehouse using Data Envelopment (DEA) method. The scope of this study is to focus on the evaluation performance efficiency value of warehouse. The time frame covered is one year which is in year 2014/2015. This study is conducted by using DEA software which we used CCR model to measure the efficiency of decision making units (DMUs) which we use the warehouse as the DMUs. It is a quantitative study which the performance efficiency of the warehouse is measured based on the variables of the input and output. The results of the CCR Model of the efficiency of the warehouse which is efficient was determined and use as the benchmark to the other warehouses. The improvement of the warehouse has been recommended by include as many DMUs as possible because with a larger population there is a greater probability of capturing high performance units that would improve discriminatory power.